Local Self-Government in Kosovo: The Impact of International Agreements on the Association of Municipalities with a Major Serb Population - Bashkim Rrahmani; Majlinda Belegu (Studia Regionalne i Lokalne)
This paper aims to explain the organisation and functioning of local governance based on the legal infrastructure of Kosovo and the efforts of its institutions to accommodate international pressure under the existing legal infrastructure, which was specifically created according to international law and international demands. Kosovo has implemented asymmetric decentralisation, through which new special municipalities have been created for minorities, with a specific emphasis on the Serb minority. This was undertaken with the aim of integrating minorities into Kosovo’s constitutional-political system; this objective has been realised quite well, with the exception of four municipalities in the north of Kosovo. All minorities are well integrated, including the Serb minority living in the south of Kosovo. However, pressure for the creation of an Association of Serb Municipalities continues, despite the request for such an association violating Kosovo’s system and constitution, which were created in line with international law and international demands. After elaborating on the Kosovo system, this study will explain certain agreements that, had they been non-ambiguous, would have helped and strengthened Kosovo’s constitutional and political system. A combined methodology, followed by legal, historical, and teleological analyses, supported the authors in achieving the study’s.